Peran Pemimpin dalam Penerapan Telenursing Guna Meningkatkan Kualitas Pelayanan Kesehatan di Era Digitalisasi - Eva Oktaviarini; Rr Tutik Sri Hariyati (Journal of Telenursing (JOTING), 2023)
This study aims to identify the role of the leader in deciding how telenursing will be used in the medical field. The research method used in this study is a literature review using the Scopus database, clinical key, and research plans using nursing terms. The results of this study highlight the importance of digital leadership. Nursing information technology can improve the standard of care. In conclusion, telenursing benefits patients, nurses, and the government. The nurse's knowledge and skills must complement this. To use telenursing, nurses must be familiar with current technology. As information technology develops, here the role of the leader is vital in increasing team members' knowledge on how to use telenursing to provide nursing care services to patients. Keywords: Leader, Information Technology, Telenursing